St. Denis Medical. Season one [videorecording (DVD)]. - McLendon-Covey, Wendi, 1969-; Grier, David Alan, 1956 June 30-; Tolman, Allison; Leeper, Mekki (Universal Pictures Home Entertainment, 2025)
At St. Denis Medical Center, the dedicated doctors and nurses are trying their best to treat patients without completely losing their own minds. Overworked and often underappreciated, these everyday heroes are busy saving lives with a healthy dose of humor and heart.